2020
DOI: 10.1007/s11356-020-10687-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cynara cardunculus L. and municipal solid waste compost for aided phytoremediation of multi potentially toxic element–contaminated soils

Abstract: The suitability for aided phytoremediation of Cynara cardunculus L. var. altilis and municipal solid waste compost (MSWC) applied at 2% and 4 % rates was evaluated in a multi potentially toxic element (PTE)-contaminated mining soil (Pb ~ 15,383 mg kg−1, Zn ~ 4076 mg kg−1, As ~ 49 mg kg−1, Cd ~ 67 mg kg−1, Cu ~ 181 mg kg−1, and Sb ~ 109 mg kg−1). The growth of C. cardunculus significantly increased with compost amendment and followed the order: MSWC-4% > MSWC-2% > Control. PTE concentrations in the roots … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…By contrast, As accumulation in shoots of P. australis and A. donax grown in MSWC-amended soils was comparable and in some cases significantly lower than that observed in plants grown on control soils (Castaldi et al, 2018). Garau et al (2020) reported a significant decrease in the concentration of different PTE in cardoon tissues grown in soil treated with 2% and 4% (w/w) MSWC. For example, As concentration in roots decreased by 11.7-fold and 8.7-fold, and Sb by 6.7-fold and 6.5-fold, in 2% and 4% (w/w) amended soils respectively, compared to control (unamended) roots.…”
Section: Accepted Papermentioning
confidence: 74%
See 4 more Smart Citations
“…By contrast, As accumulation in shoots of P. australis and A. donax grown in MSWC-amended soils was comparable and in some cases significantly lower than that observed in plants grown on control soils (Castaldi et al, 2018). Garau et al (2020) reported a significant decrease in the concentration of different PTE in cardoon tissues grown in soil treated with 2% and 4% (w/w) MSWC. For example, As concentration in roots decreased by 11.7-fold and 8.7-fold, and Sb by 6.7-fold and 6.5-fold, in 2% and 4% (w/w) amended soils respectively, compared to control (unamended) roots.…”
Section: Accepted Papermentioning
confidence: 74%
“…Root biomass of C. cardunculus increased by more than 17-fold and 23-fold in polluted soils amended with 2% and 4% (w/w) MSWC respectively, compared to unamended soil, while shoot biomass increased by approx. 5-fold and 10-fold (Garau et al, 2020).…”
Section: Accepted Papermentioning
confidence: 96%
See 3 more Smart Citations